Analysis of association of the anthropometric, motor and functional parameters on competitive efficiency in youth football players - Škomrlj, J.; Versic, S.; Foretic, N. (SportMont, 2022)
In a complex team sport setting, such as during a football game, the match`s outcome is determined by numerous factors, such as the technical, tactical, physical and psychological preparedness of all the players, who have to act like a unit. This study aimed to identify anthropometric characteristics and motor and functional abilities that affect the competitive efficiency of U-15 football players. A total of 20 football players, classified either as starters (N=10) or non-starters (N=10), underwent morphologic measurements comprising body height and body weight and motoric assessments and testing of functional capacity: 5-meter sprint, 10-meter sprint, 20-meter sprint, broad jump, medicine ball throw, and triple jump on the left and right legs. Additionally, the age of peak height velocity (APHV) was calculated for each participant. The results showed that the body weight (OR:0.86; 95%CI:0.75-0.99) and medicine ball throw (t=2.24; p=0.02) were significant predictors of one`s competitive efficiency in the observed sample of young football players. Since upper body power is highly influenced by anthropometric characteristics at this age, starters will most likely receive more playing time and have superiority over their peers due to morphologic advantages. This study once again confirmed that early maturing players have an advantage over others because of their body size, which seems to be a significant determinant of success at that age.